Chromoendoscopic surveillance in hereditary diffuse gastric cancer: an alternative to prophylactic gastrectomy?. Issue 4 (7th March 2005) - Shaw, D; Blair, V; Framp, A; Harawira, P; McLeod, M; Guilford, P; Parry, S; Charlton, A; Martin, I
Abstract : Background: Hereditary diffuse gastric cancer (HDGC) is defined by germline mutations in the E-cadherin gene, CDH-1 . The first family in which CDH-1 mutations were identified was a large Maori kindred, where lifetime penetrance is 70%. Prophylactic gastrectomy is an unacceptable option for many mutation carriers. The results of annual chromoendoscopic surveillance using the methylene blue/congo red technique in 33 mutation carriers over a five year period are described. Patients and methods: Thirty three confirmed CDH-1 mutation carriers (18 males, 15 females), median age 32 years (range 14–69), were enrolled in 1999–2003. Medical records, endoscopy, and pathology were reviewed retrospectively. Results: Over five years, 99 surveillance endoscopies were performed, of which 93 were chromo-dye enhanced. Sixty nine chromoendoscopies were normal. In 24 procedures, 1–6 pale areas/stomach (size 2–10 mm) were detected post chromo-dye application (totalling 56 pale lesions). One biopsy was taken from each pale lesion: 23 lesions (41%) showed signet ring cell carcinoma (10 patients), 10 lesions (18%) gastritis (four patients), and 23 (41%) normal mucosa (10 patients). No chromo-dyes were used in six procedures with macroscopic lesions (two HDGC, four ulceration). Total gastrectomies from patients with carcinoma were macroscopically normal but pathological mapping showed multiple microscopic foci of early signet ring cell carcinoma. Correlation of chromoendoscopic and gastrectomy findings showed that congo red/methylene blue detected carcinoma foci 4–10 mm in size but not foci <4 mm. Conclusions: The use of chromoendoscopy following normal white light gastroscopy facilitated detection of early gastric carcinoma foci not visible with white light gastroscopy. If these findings are validated in other HDGC kindred, chromogastroscopy represents an improved surveillance technique that can be safely considered alongside prophylactic gastrectomy.